Percutaneous Ablation of Benign Thyroid Nodules as Safe Alternative for Surgery: A Single-Center Experience - Padmaraju, Vinay Thondaebhavi; TP, Prafulla; Uthappa, Mangerira Chinnappa (Journal of Clinical Interventional Radiology ISVIR, 2025)
The increasing prevalence of thyroid nodules, coupled with the desire to minimize the invasiveness and potential complications associated with surgical interventions, underscores the critical need for exploring alternative therapeutic strategies.To evaluate the role of percutaneous radiofrequency ablation in the management of benign thyroid nodules.Forty-five consecutive patients who presented with evidence of symptomatic benign thyroid nodules and were categorized under TIRADS 1 or 2 and BETHESDA II scoring were selected for percutaneous ablation.About 86.7% were women with a mean (±standard deviation [SD]) age being 44.4 (± 5.4) years. Radiofrequency ablation was done for 45 patients with solid or predominantly solid thyroid nodules. Majority of them (79.66%) reported a reduction in symptom score after ablation. The mean (± SD) volume of the nodules at baseline was 35.03 (± 17.2) mL, which significantly (p = 0.05) dropped to 7.44 (± 4.1) mL at 1 year of follow-up. The average volume reduction rate was 79.66% at 1 year, with the maximum rate of volume reduction observed at the first month of follow-up.Percutaneous radiofrequency ablation is a safer and an effective alternative to surgery for managing benign thyroid nodules.
Keywords: minimally invasive surgical procedures; radiofrequency ablation; thyroid nodule; ultrasound